APPLYING MULTIDIMENSIONAL CANONICAL PARTITIONING (MCP) APPROACH TO DESIGN URBAN DECISION-SUPPORT SYSTEM - Apollinaire Bamana Batoure; Michel Tchotsoua; Kolyang Kolyang (Bakti Nusantara Institute, 2022)
The design of decision-support systems remains a challenge because no method has yet been approved, although several approaches have been proposed. Multidimensional Canonical Partitioning (MCP) is a supply-driven approach to design decision-support systems, previously proposed. In this approach, decision systems are designed from Entity/Relationship (E/R) schema. The schema provided as input is reduced to a flat relation, if it is not already the case, by using universal relations assumption. The design approach uses two main algorithms. The first is a greedy type heuristic algorithm, and the second a matching algorithm. The approach has six steps. In this paper, we implement algorithms used in the design approach. We then propose a graphical interface as a tool for implementing the approach. The tool, called PaCaM, is intended to be used by decision-support systems designers. We after all apply the design approach on urban transactional systems.